PTH-056 Novel Model of Care: The Impact of A Combined IBD & Antenatal Clinic. (17th August 2016) - Selinger, C; Carey, N; Ulivi, G; Walker, L; Shaikh, F; Glanville, T
Abstract : Introduction: Care for pregnant women with IBD requires complex decision making weighing the risks and benefits of medication. Patients are often exposed to conflicting information from different health care professionals. This novel IBD antenatal clinic provides multidisciplinary care with an IBD clinician, an IBD nurse and an obstetrician all present during the consultation. Methods: Prospective data collection for all patients attending the clinic from March 2014 to September 2015 included IBD diagnosis, treatment, adherence (MARS self report scale), disease & pregnancy related patient knowledge (CCPKnow), course of pregnancy, mode of delivery and breast feeding. Patient satisfaction (1 not to 5 very satisfied) was ascertained by formal feedback weeks after delivery. Results: Of 48 women (mean age 32 years; range 21–43) 27 had Crohn's disease, 17 ulcerative colitis and 4 IBD-unclassified. Medication exposure during pregnancy included 5 ASA in 19, Thiopurines in 22 and anti-TNF in 11 cases (3 ongoing, 1 continued to birth, 7 stopped at mean week 25). Disease severity during pregnancy was remission in 62%, mild in 18%, moderate in 16% and severe in 4%. Poor medication adherence occurred in 5 of 27 patients providing adherence data. IBD investigations during pregnancy included 2 bowel ultrasound scans, 1 MRI and 2 sigmoidoscopies. Mean CCPKnow scores were 8.9 at 1 st consultation and 10.1 after birth. Two patients attended for pre-pregnancy counselling and 15 are currently pregnant. There were 27 (17 female) live births, 2 miscarriages, 1 intra-uterine death and 1 medically indicated termination for cardiac abnormalities. Delivery occurred on average at week 39 (range 29–41) with only 2 births before 35 weeks gestation. 19 (70%) patients had a vaginal delivery (5 assisted), 3 underwent elective and 5 emergency caesarean section. Average birth weight was 3099 gram (4 weighed less than 2500 g) and only 3 babies were on the 5 th percentile on personalised growth charts. 18 (66.6%) of mothers breastfed the infant. The average patient satisfaction score was 4.6. Conclusion: This novel clinic model offers unique care for pregnant women with IBD. We have demonstrated very good IBD, obstetric and neonatal outcomes. Medication adherence was at least equivalent to non-pregnant patients. In contrast to previous studies showing high caesarean section and poor breast feeding rates in women with IBD our results were close to the national average for healthy women. As patient satisfaction was also high a wider adoption of the model should be considered. Disclosure of Interest: C. Selinger Grant/research support from: Abbvie, Warner Chilcott, Consultant for: Abbvie, Warner Chilcott, MSD, Takeda, Speaker bureau with: Abbvie, Warner Chilcott, Dr Falk, Takeda, N. Carey: None Declared, G. Ulivi: None Declared, L. Walker: None Declared, F. Shaikh: None Declared, T. Glanville: None Declared